ИЗУЧЕНИЕ ВИДОВ УЧЕБНОГО ФИЗИЧЕСКОГО ЭКСПЕРИМЕНТА И ЕГО ЗАДАЧИ В СРЕДНИХ СПЕЦИАЛЬНЫХ УЧЕБНЫХ ЗАВЕДЕНИЯХ (Scientific journal of the Fergana State University, 2023)
This article discusses how to prepare students of secondary special educational establishments the development of new technology, new technological processes with which they will have to deal with in practice.